KOMBINASI PUPUK ORGANIK CAIR (POC) KULIT BAWANG PADA BERBAGAI MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL MENTIMUN BABY (Cucumis sativus L. Var. Vanesa) - mochamad alex; Anis Sholihah; Abdul Basit (AGRONISMA, 2022)
This study aims to determine the application of liquid organic fertilizer (POC) to various growing media on the growth and yield of baby cucumbers. The study used a factorile randomized block design (RAK) with control, the first factor consisted of 2 levels, namely P1, = POC of onion skin and P22 = POC of garlic skin while the second factor consisted of 3 levels M1 = Soil + Husk (: 1 ), M2 = Soil + Mushroom Blog Waste (2 : 1 ), M3 = Soil + cow manure (2 : 1 ) so that 6 combinations and 1 control were obtained so that there were 7 treatments which were repeated 3 times. The results showed that garlic peel POC gave a better response than POC on cucumber growth and yield variables. The combination of POC treatment of garlic peel and cow dung gave a value of 35.54 cm at the length of the plant at 21 DAP, the number of fruit per plant was 17.50 units, fruit weight per plant and fruit weight per hectare were 303.33 g and 30,69 ton/ha.Keywords: POC onion skin, planting medium, baby cucumber, mushroom baglog waste